Promoting sustainable development through digital trade and digital trade policies - Paul R. Baker; Loan Le (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2023)
This paper examines the role of digital trade policy in promoting sustainable development. It starts from the conceptual framework of digital trade, as well as the interplay between digital transformation and the roles of trade and investment as means to achieving the Sustainable Development Goals (SDGs). This is supported by examination of the growth in digital trade, with special attention to Developing Countries (DCs) and Least Developed Countries (LDCs), and broad inferences regarding the implications for more inclusive and sustainable development. Drawing from the analysis on the pathways linking digital trade and SDGs, the paper identifies policy measures that could help unleash the benefits of digital trade across different sectors with respect to sustainable development. These include digital trade facilitation measures that may be taken to reduce the environmental impact of trade procedures and to enhance digital trade opportunities for women and Micro, Small and Medium Enterprises (MSMEs)
hdl:20.500.12870/6640
Keywords: F10; F13; Q01; 330; Sustainable development; SDGs; digital trade; trade policies; trade facilitation